Smaller public sectors in the Euro area: Aggregate and distributional implications - George Economides; Dimitris Papageorgiou; Apostolis Philippopoulos; Vanghelis Vassilatos (Center for Economic Studies and ifo Institute (CESifo), 2012)
In this paper, we study the aggregate and distributional implications of a smaller public sector in the euro area. By a smaller public sector, we mean a reduction in public debt and/or cuts in public spending, when such changes in fiscal policy are accommodated by adjustment in various taxes. Aggregate implications have to do with per capita output and welfare, while distribution refers to differences in income and welfare between private and public sector employees. We solve the model numerically using fiscal data from the euro area and then do a number of policy experiments. The general message is that the issue is not just a smaller public sector, but also the spending-tax mix chosen.
Keywords: H10; H20; H30; 330; size of public sector; debt consolidation; taxation; reforms; Haushaltskonsolidierung; Staatsquote; Makroökonomischer Einfluss; Verteilungswirkung; Eurozone